A Mobilidade de Pacientes Obesos no Pós-Cirúrgico Bariátrico - Koyama, Renata Emy (2007)
The person with morbid obesity has serious health problems , due to it may occur organic diseases, adverses psychosocial mainly caused by the affected personal mobility. The day-by-day of a morbid obese person is very difficult, due to the lack of mobility, activities like to take shower, to get dressed, to tie the shoes, to walk from a place to another ( because it´s breathtaking ), to enter in a vehicle, to go upstairs and to sit in unapropriated chairs, become hard. This way, the bariatric surgery arises as an invasive and extreme treatment, resulting in loss of weigth in a short period of time, modifying quickly the physical structure causing psychological and social changes to the person; and the mobility of the person after some months of the surgery can be modified. The objective of this work in a phenomenonlogic focus is to identify the meaning of mobility for obeses patients after the bariatric surgery, faced with the fast corporal change; being important the psychological treatment after the surgery and the relation of mobility in this context, to contribute with more information about the difficulties the patients go through. The results that were found about the meaning of mobility three months after bariatric surgery are: joy, happiness, victory, they felt like another person and better than before, the most important thing in life and all